Two graves [compact disc, unabridged] - Preston, Douglas J. (Preston, Douglas J. Pendergast novel., 2012)
After his wife, Helen, is brazenly abducted before his eyes, Agent Pendergast furiously pursues the kidnappers. But then, things go terribly, tragically wrong; the kidnappers escape; a shattered Pendergast retreats to his New York apartment and shuts out the world. But when a string of bizarre murders erupts across several Manhattan hotels, Lieutenant D'Agosta asks Pendergast for help. Reluctant at first, Pendergast soon discovers that the killings are a message from his wife's kidnappers.